The pharmacological management of acute behavioural disturbance: Data from a clinical audit conducted in UK mental health services. (April 2019) - Paton, Carol; Adams, Clive E; Dye, Stephen; Fagan, Elizabeth; Okocha, Chike; Barnes, Thomas RE
Background: A quality improvement programme addressing prescribing practice for acutely disturbed behaviour was initiated by the Prescribing Observatory for Mental Health. Method: This study analysed data from a baseline clinical audit conducted in inpatient mental health services in member trusts. Results: Fifty-eight mental health services submitted data on 2172 episodes of acutely disturbed behaviour. A benzodiazepine alone was administered in 60% of the 1091 episodes where oral medication only was used and in 39% of the 1081 episodes where parenteral medication (rapid tranquillisation) was used. Haloperidol was combined with lorazepam in 22% of rapid tranquillisation episodes and with promethazine in 3%. Physical violence towards others was strongly associated with receiving rapid tranquillisation in men (odds ratio 1.74, 1.25–2.44; p <0.001) as was actual or attempted self-harm in women (odds ratio 1.87, 1.19–2.94; p =0.007). Where physical violence towards others was exhibited, a benzodiazepine and antipsychotic was more likely to be prescribed than a benzodiazepine alone (odds ratio 1.39, 1.00–1.92; p =0.05). The data suggested that 25% of patients were at least 'extremely or continuously active' in the hour after rapid tranquillisation was administered. Conclusion: The current management of acutely disturbed behaviour with parenteral medication may fail to achieve a calming effect in up to a quarter of episodes. The most common rapid tranquillisation combination used was lorazepam and haloperidol, for which the randomised controlled trial evidence is very limited. Rapid tranquillisation prescribing practice was not wholly consistent with the relevant National Institute for Health and Care Excellence guideline, which recommends intramuscular lorazepam on its own or intramuscular haloperidol combined with intramuscular promethazine. Clinical factors prompting the use of rapid tranquillisation rather than oral medication may differ between the genders.